Participatory visual methods and school-based responses to HIV in rural South Africa: insights from youth, preservice and inservice teachers - MacEntee, Katie (Sex Education: Sexuality, Society and Learning, 2020)
This paper explores students', preservice teachers' and inservice teachers' perceptions of the contributions and challenges of using participatory visual methodologies (PVM) to enhance HIV education in rural schools. Drawing on findings from three research projects conducted in KwaZulu Natal, South Africa, four positive contributions are identified: 1) novelty, fun and engagement; 2) amplifying youth voices; 3) the facilitation of teachers' reflexive learning; and 4) the production of local resources in under-resourced schools. Challenges include: 1) limited technology access; 2) teacher discomfort; and 3) resistance to PVM integration. Teachers and young people, especially in under resourced rural settings, can benefit from integrating such methodologies into their responses to HIV and AIDS. However, sustainable integration must rely on choosing the most appropriate participatory visual methodologies given the technological resources available in school. The paper concludes with recommendations to optimise participatory visual methodologies integration into rural school-based HIV responses.
Keywords: Acquired Immunodeficiency Syndrome (AIDS); Children And Youth - About; Disadvantaged Schools; ERIC, Current Index to Journals in Education (CIJE); Educational Resources; Foreign Countries; HIV; Health Education; Higher Education; Media Selection; Photography; Postsecondary Education; Preservice Teachers; Rural Schools; Secondary Education; Secondary School Students; Sex Education; South Africa; Story Telling; Student Attitudes; Teacher Attitudes; Teaching Methods; Visual Aids; __:import:01; __:match:final; __:matched; __:study_id:2096729; __finaldtb; participatory visual methodology; rural education; sexual health education